Foundations of Islāmic psychology: from classical scholars to contemporary thinkers - Rassool, G. Hussein (Routledge, Taylor & Francis Group, 2023)
Section I: Foundation & Revival of Islāmic Psychology: 1. Foundation of Islāmic Psychology: The 'Dodo Bird' Revival -- 2. The Golden Age of Islam -- 3. Islamisation of Knowledge in the Evolution of Islāmic Psychology -- Section II: Classical Scholars: Philosophers, Physicians and Theologians: 4. Abu Yusuf Yaqub Ibn Ishaq Al-Kindī -- 5. Ibn Miskawayh, Ibn Rushd and Al Fārābī -- 6. Abdu Bakr Mohamed Ibn Zakariya Al-Rāzī -- 7. Abu Zayd Ahmed ibn Sahl al-Balkhī -- 8. Abu Ali al-Husayn Ibn Abdullah Ibn Sīnā -- 9. Abu Hamid Muhammad al-Ghazālī -- 10. Ibn Taymiyyah al-Ḥarrānī -- 11. Ibn Qayyim al Jawziyyah --12. Al-Raghib Ar-Rāghib al-Aṣbahānī --13. Jamāl al-Dīn Abū al-Faraj ʻAbd al-Raḥmān Ibn al-Jawzī --14. Ibn Khaldūn al-Ḥaḍramī --15. Ibn Rajab al-Hanbali --Section III: 19-21st Scholars, Academics & Clinicians: 16. Allama Muhammad Iqbal (Pakistan) --17. Malik Badri, his contributions to the revival of Islāmic Psychology (Sudan) --18. Amber Haque (US/India) --19. Rasjid Skinner (UK) -- 20. Akhbar Husain (India) -- 21. Rania Awaad (US/ Egypt) -- 22. Muhammad Tahir Khalily (Pakistan) -- 23. Suleyman Derin (Turkey) -- 24. Hamid Rafiei Honar (Iran) -- 25. Saleh bin Ibrahim Al-Sanie (Saudi Arabia) -- 26. Ola Pavova (Russia) -- 27. G. Hussein Rassool (UK/Mauritius) -- Section IV: Epilogue: 28. Shifting the Paradigm: Decolonising Psychology Knowledge -- 29. Islāmic Psychology Promising Past and Challenging Future.